(untitled) (Dermatology Reports, 2023)
Rarely, the gram-negative bacteria Klebsiella pneumoniae causes skin infections that are frequently challenging to identify. We present a case of an atypical presentation of this specific disease in terms of its site, lack of risk factors, and length of illness.